Risk of subsequent biliary malignancy in patients undergoing cyst excision for congenital choledochal cysts. Issue 2 (22nd January 2013) - Ohashi, Taku; Wakai, Toshifumi; Kubota, Masayuki; Matsuda, Yasunobu; Arai, Yuhki; Ohyama, Toshiyuki; Nakaya, Kengo; Okuyama, Naoki; Sakata, Jun; Shirai, Yoshio; Ajioka, Yoichi
Abstract Background and Aim The aim of this study was to elucidate the risk of subsequent biliary malignancy in patients undergoing cyst excision for congenital choledochal cysts. Methods A retrospective analysis of 94 patients who had undergone cyst excision for congenital choledochal cysts was conducted. The median age at the time of cyst excision and median follow‐up time after cyst excision were 7 years and 181 months, respectively. Results Biliary tract cancer developed in four patients at 13, 15, 23, and 32 years after cyst excision. The cumulative incidences of biliary tract cancer at 15, 20, and 25 years after cyst excision were 1.6%, 3.9%, and 11.3%, respectively. The sites of biliary tract cancer were the intrahepatic (n = 2), hilar (n = 1), and intrapancreatic (n = 1) bile ducts. Of the four patients with biliary tract cancer after cyst excision, three patients underwent surgical resection and one patient received chemo‐radiotherapy. The overall cumulative survival rates after treatment in the four patients with biliary tract cancer were 50% at 2 years and 25% at 3 years, with a median survival time of 15 months. Conclusions The risk of subsequent biliary malignancy in patients undergoing cyst excision for congenital choledochal cysts seems to be relatively high in the long‐term. The risk of biliary malignancy in the remnant bile duct increases more than 15 years after cyst excision. Despite an aggressive treatment approach for this condition, subsequent biliary malignancy following cyst excision for congenital choledochal cysts shows an unfavorable outcome.